Option Introduction and Liquidity Changes in the OTC/NASDAQ Equity Market - Rich Fortin; Judy Maese (Journal of Small Business Finance, 1992)
This paper examines the impact of option listing in the NASDAQ equity market on the bid-ask spread of the underlying stock. We find that both the market adjusted percentage and dollar spreads decrease with option listing, which is consistent with a value enhancing impact of derivative security introduction.
Keywords: G13; G12; 650; NASDAQ; Nasdaq; Options; OTC; Liquidity